1994
DOI: 10.1620/tjem.172.227
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Diastolic Filling in the First Day of Life.

Abstract: To evaluate the effects of altered preload on the Doppler flow pattern of right ventricular inflow in the first day of life, serial Doppler echocardiography of the pulmonary artery (PA) and tricuspid valve was performed in 16 normal neonates at 2, 12, and 24 hr. A computerinterfaced digitizer pad was utilized to measure the followings: PA flow velocitytime integral, total transtricuspid flow velocity-time integral, flow velocity-time integral of early diastolic filling (E area), and flow velocity-time integral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…The early decrease that was observed in the Tei index most likely reflects the alterations in cardiac loading that result from the increase in pulmonary blood flow attendant to the onset of pulmonary ventilation. The transition to postnatal circulation includes a sudden decrease in pulmonary vascular resistance and shift of cardiac output from the right to left ventricle 27 –29 …”
Section: Discussionmentioning
confidence: 99%
“…The early decrease that was observed in the Tei index most likely reflects the alterations in cardiac loading that result from the increase in pulmonary blood flow attendant to the onset of pulmonary ventilation. The transition to postnatal circulation includes a sudden decrease in pulmonary vascular resistance and shift of cardiac output from the right to left ventricle 27 –29 …”
Section: Discussionmentioning
confidence: 99%
“…5 On the other hand, Ew of the mitral annulus did not change significantly. Harada and colleagues 6 reported that tricuspid E increases within 24 hours after birth, probably due to an increase in the right ventricular preload and decreased right ventricular afterload. Ew of the tricuspid annulus did not change significantly during this period, unlike Ew of the mitral annulus.…”
Section: Diastolic Wall Motion Velocitymentioning
confidence: 99%
“…There are several reports concerning changes in the mitral and tricuspid flow patterns during the neonatal period. [4][5][6] On the other hand, tissue Doppler echocardiography allows the recording of myocardial contraction and relaxation velocity. Pulsed wave Doppler tissue (PWDT) echocardiography can be used to analyse the long axis function of both ventricles, which is difficult to evaluate by conventional echocardiographic methods.…”
mentioning
confidence: 99%
“…This discrepancy may reflect differences in developmental changes in the diastolic properties of the myocardium between the two ventricles, poorer RV compliance 20,21 and in-utero right heart dominance 22 .…”
Section: Discussionmentioning
confidence: 99%